Research progress on the mechanism of glycolysis in ovarian cancer - Li, Chan; Liu, Fang-Yuan; Shen, Ying; Tian, Yuan; Han, Feng-Juan (Frontiers in Immunology, 2023)
Glycolysis is the preferred energy metabolism pathway in cancer cells even when the oxygen content is sufficient. Through glycolysis, cancer cells convert glucose into pyruvic acid and then lactate to rapidly produce energy and promote cancer progression. Changes in glycolysis activity play a crucial role in the biosynthesis and energy requirements of cancer cells needed to maintain growth and metastasis. This review focuses on ovarian cancer and the significance of key rate-limiting enzymes (hexokinase, phosphofructokinase, and pyruvate kinase, related signaling pathways (PI3K-AKT, Wnt, MAPK, AMPK), transcription regulators (HIF-1a), and non-coding RNA in the glycolytic pathway. Understanding the relationship between glycolysis and these different mechanisms may provide new opportunities for the future treatment of ovarian cancer.